Algunas interpretaciones de la Ilustración y su relación con Hegel : La radicalización de la autonomía racional como inmanentización de toda trascendencia - Sisto, Horacio Martín
Regarding the twentieth century's interpretations of the Enlightenment and its actuality, it is noteworthy that some authors, like Habermas in "The philosophical discourse of Modernity", rely on Hegel to defend the Enlightenment and its project, whereas other close thinkers, like Adorno and Horkheimer in their "Dialectic of Enlightenment", quote Hegel to emphasize the destructive aspects of Enlightenment. In this work I show that in the Hegelian theory of Enlightenment both aspects, the negative and the programmatic, are present. I hold here that the Hegelian philosophy claims to be the consummation and not the rupture with this movement. This is expressed in the subtitle of the thesis: in the philosophy of Hegel the principle of autonomy is made absolute in terms of an immanentization of any transcendence that could have been still recognized or latent in the thought of the Enlightenment. For a theory of the Enlightenment I consider as reference the exposition of Cassirer, "The Philosophy of the Enlightenment ". As reference texts of the Hegelian philosophy I follow principally passages from "The Phenomenology of Spirit" and "Glauben und Wissen".